Penggunaan neraca berfikir al-Ghazali pada menilai pemikiran Shiah Ismailiyyah Batiniyyah Ta‘limiyyah tentang sumber al-Ma‘rifah dalam kitab al-Qistas al-Mustaqim / Mariam Abdul Rahman - Mariam , Abdul Rahman (2018)
Confusion in response to meaning has become an issue in the study of al-ma‘rifah, despite having similar terms. The source of al-ma‘rifah as understood by the Shī‘ah al-Ismā‘īlīyyah alBāṭinīyyah al-Ta‘līmīyyah have different interpretations from that of al-Ghazālī. In this respect, this thesis has three main objectives. First, is to identify the position of the flow and balance of Shiites thinking that underlie their thought. The second objective is to explore the function of mawāzīn al-Qur’ān used by al-Ghazali as the source of al-ma‘rifah. Third, is to study the use of balance thinking of al-Ghazali’s belief on Shī‘ah flow that considered their imam as the source of al-ma‘rifah. This research is based on the descriptive text methodology. Overall, the study uses qualitative method of data collection utilizing inductive and deductive techniques. Comparative methods were also used in the data analysis. The outcome of this research found that the right leadership among Shī‘ah al-Ismā‘īlīyyah al-Bāṭinīyyah al-Ta‘līmīyyah has a dominant position because the imam possess the highest religious authority and are infallible. The belief on the flow of the infallibility of the Shī‘ah imams, who inherited their power since the death of the Prophet, has led to the understanding that imam is the source of al-ma‘rifah. To assess the validity of this thought, al-Ghazālī introduces mawāzīn al-Qur’ān as a source of ma‘rifah which is based on Qur’anic foundation. By adopting mawāzīn as an approach to the flow of Shī‘ah’s thought, this research discovers a confusion in understanding the nature of things which is due to two factors ; firstly, errors of facts and information ; and, secondly : Shī‘ah understanding of al-ma‘rifah do not meet the conditions set out by the Qur’anic sources.